Bibliometric Analysis of Islamic Macroeconomic Publication Trends Using VOSviewer - Rozalinda, Rozalinda; Augusna, Wahyuni Lely; Wira, Ahmad; Azis, Saipul (International Journal of Islamic Studies Higher Education, 2024)
This research aims to analyze the topics of articles published in Google Scholar and Dimensions journals with the keyword "Islamic macroeconomics" and identify the extent of the development of research on Islamic macroeconomics and its relation to various fields as well as analyze new topics that are novel so that they can be developed for further research. This research is quantitative research with bibliometric analysis. This research data is secondary data in the form of a journal database from Google Scholar and Dimensions. The research results show that the Google Scholar database based on network visualization analysis proves that there is a link between macroeconomics and Islamic macro indicators and variables in general. This finding is proven by the many Islamic macroeconomics variables found in each cluster. In the density visualization analysis, there are the terms of inflation, conventional bank, return and Islamic finance, which are topics that have been widely researched during 2014-2023. Meanwhile, in the database dimensions in the network visualization analysis shows that Islamic banking, financing, and exchange rates are closely interconnected. New contributions from this research include identifying emerging topics such as zakat, Islamic commercial banks, Islamic capital markets, Islamic stock markets, and Islamic stocks. Using the ARDL method and density visualization analysis, this study concludes that Islamic banking is the most frequently discussed topic in relation to Islamic macroeconomics.